Analytical Lexicon of the Greek Bible - Gieniusz, Andrzej (Eastern and Central European Voices. Supplements, 2023)
The basic forms of the Greek Bible put in alphabetical order create the lexicon’s entries. Every entry has its English translation along with the number of occurrences of the Greek term in the Septuagint, parallel texts and in the New Testament with the sum of all occurrences in all the Bible. At the end of each entry the lexical forms of it are given and listed in alphabetical order with a grammatical analysis and occurrences throughout the Scriptures.In the dictionary, as it is in the concordance, four colours are given a new category of distinction. They separately characterize the texts and references of the Septuagint (green), parallel texts (red) and the New Testament (blue). The same colours are attributed to the number of appearances of the terms in the text. The terms are presented in the Dictionary firstly in basic form, then in all lexical forms arranged in alphabetical order.